2011
DOI: 10.1007/978-3-642-20841-6_37
|View full text |Cite
|
Sign up to set email alerts
|

Constrained LDA for Grouping Product Features in Opinion Mining

Abstract: Abstract. In opinion mining of product reviews, one often wants to produce a summary of opinions based on product features/attributes. However, for the same feature, people can express it with different words and phrases. To produce an effective summary, these words and phrases, which are domain synonyms, need to be grouped under the same feature. Topic modeling is a suitable method for the task. However, instead of simply letting topic modeling find groupings freely, we believe it is possible to do better by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…However, Zhai et al [28] proposed another semi-supervised method known as constrained-LDA [24] that does not need any pre-labeled data as initial seed. Constrained-LDA is an extension of LDA method with the ability to consider existing knowledge in the form of must-link and cannot-link constraints.…”
Section: Semi-supervised Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Zhai et al [28] proposed another semi-supervised method known as constrained-LDA [24] that does not need any pre-labeled data as initial seed. Constrained-LDA is an extension of LDA method with the ability to consider existing knowledge in the form of must-link and cannot-link constraints.…”
Section: Semi-supervised Approachesmentioning
confidence: 99%
“…This observation allows us to extract many "cannot-link" constraints automatically. Secondly for "must-links", it can be observed that two noun phrases that shared one or more words are likely to fall into the same topic, e.g., "battery life", "battery consumption" and "battery power" [28].…”
Section: Semi-supervised Approachesmentioning
confidence: 99%
“…Thus the sellers can be ranked efficiently as if ranking is done manually. The correlation between natural (manual) clustering and CommTrust clustering [13] was checked using Kendall"s τ measure. The correlation was found positive i.e.…”
Section: Dmentioning
confidence: 99%
“…• Constraint-LDA: Constraint-LDA (Zhai et al, 2011b) is a state-of-the-art LDA-based method that incorporates must-link and cannot-link constraints for this task. We set the damping factor λ = 0.3 and relaxation factor η = 0.9, as suggested in the original reference.…”
Section: Comparison To Unsupervised Baselinesmentioning
confidence: 99%